Mergers and acquisitions : the case of Merck & Co and Schering-Plough Corporation - Teixeira, Nádia Sofia Tavares (2013)
The global pharmaceutical industry is characterized for being highly competitive and for having though market regulations. Therefore, companies whose seek to generate value and continue with a strategic position in the market, look for different and smart ways to achieve the objective. In this industry, Mergers and Acquisitions are very supported by practitioners and managers, since it enhance the productivity of the company and the shareholder value. Merck & Co., Inc and Schering-Plough Corporation are an example of the merger of two companies that brought and incorporated different capabilities in an efficient way, therefore taking advantage of new opportunities in the different segments of the pharmaceutical industry. The goal of this dissertation is to do the historical financial analyze and estimate the enterprise value of both companies as if they were optimally managed; and assess the value of the merged entity and the synergies created. Last it is proposed an acquisition mode and optimal price for the deal to be accepted. Through the Literature Review it is presented explained the different valuation methods and M&A concepts and applications. This work showed that Merck & Co., Inc and Schering-Plough Corporation were undervalued during 2008, and the merger will create value of both companies. The estimated synergies, approximately $ 84 billion, represent 26 percent of the merged entity enterprise value. The company’s share price, by the end of 2008 was 30.4 and 17.03, Merck and Schering-Plough, respectively. As a result of all the valuation factors, the premium offered to Schering-Plough was 30 percent over the company’s average market capitalization, financed 51% with equity and the remaining with debt and cash.